A case of rudimentory horn ectopic pregnancy - Nalla, Sushmitha; T., Aashritha; M., Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ectopic pregnancy is emergency in obstetrics. Sometimes difficult to diagnose make it difficult to manage. There are various types of ectopic pregnancy and each possible a variety of challenges. This is a case of a 20-year-old who presented to R. L. Jalappa hospital, Kolar with history of 3 months of amenorrhea and complaints of pain abdomen. She was in state of shock and after evaluation taken up for emergency exploratory laparotomy where the diagnosis of ruptured horn ectopic of a uni-cornuate uterus was made and treated accordingly.